Process- and topography-related cell viability on laser sintered polypropylene - Schlicht, Samuel; Detsch, Rainer; Nawaz, Qaisar; Boccaccini, Aldo R.; Drummer, Dietmar (8th China-Europe Symposium on Biomaterials in Regenerative Medicine, 2024)
Purpose New manufacturing techniques, such as laser sintering of polymers, enable new biomedical applications. These new processes can also change the surface properties of materials. The relationship between the material surface and specific tissue cells can be very different. The shape and structure of biomaterial surfaces affect how cells interact with them. The objective of this study is to investigate the interaction between cells and different laser- polypropylene (PP) surfaces. This enables the correlation of processing conditions in laser-based additive manufacturing and the cell-material interaction, which is a significant prerequisite to the additive manufacturing of components with optimised surface properties for enhancing cell behaviour. Methods and Results Laser sintering of semi crystalline thermoplastics with a particular focus on polyolefines represents a promising approach to the manufacturing of geometrically complex implants with targeted mechanical properties. Constituting a fundamental prerequisite to their application, the viability and proliferation of cells in contact with such implants is of significant relevance. The present study explored the influence of macroporous, open-pored structures of varying density and pore sizes that were obtained through non-isothermal laser fusion of polypropylene particles. By varying the number of consecutive exposure cycles, the coalescence of exposed particles is modified, allowing to adapt the density gradient perpendicular to the part surface while influencing the emerging pore size distribution, yielding mean porosities of 18.8% ± 4.64, and 13.9% ± 2.91, respectively. Comparable infrared spectroscopic surface characteristics prior and subsequent to sterilization were maintained regardless of the applied laser sintering process. The present study compared the influence of varying topographic properties on the viability and corresponding morphological characteristics of NIH/3T3 fibroblasts, chondrogenic ATDC-5 cells, and C2C12 myoblasts. While NIH/3T3 fibroblasts showed a comparable viability independent on the topography of manufactured specimens, chondrogenic ATDC-5 cells and C2C12 myoblasts displayed a significantly reduced viability on polypropylene specimens of reduced pore sizes and a reduced open-pored porosity of 13.9% ± 2.91. While C2C12 myoblasts were characterized by predominantly spherical shapes, a polygonal morphology of ATDC-5 cells could be observed, with both morphologies depicting a reduced viability on denser surface structures, associated with an adapted morphology expression on denser surfaces with reduced cell adhesion. These findings indicate the significance of the macro- and mesoscopic topography of polymer surfaces, potentially allowing for influencing the proliferation and the morphological structure of adhering cells. Moreover, the cell-specific interaction with process-related topographic characteristics can be identified as a crucial aspect for the development and biological optimization of additively manufactured, polymer-based implants. Conclusion Thermographic investigations have revealed that the formation of superficial porous layers is dependent on the residual temperature induced by the core layer exposure. This enables the process-induced control of emerging topologies. The vitro study demonstrates the potential of these surfaces to produce innovative applications in the areas of muscle regeneration, wound healing and cartilage repai